2020
DOI: 10.1109/access.2020.2985978
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Power Oscillation Damping Controller for a Hybrid AC/DC Microgrid

Abstract: High penetration of dynamic loads, such as induction motors (IMs) could give rise to sustained voltage/frequency and power oscillations in hybrid AC/DC microgrids during disturbances. Majority of the published literature has investigated these stability issues with aggregated models of IMs in hybrid AC/DC microgrids, which do not properly reflect the actual dynamics of parallel operating IMs; hence, power oscillation damping (POD) controllers must be designed explicitly considering various oscillations induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The MVDC in DC microgrid application is illustrated in [18], covering AC interfaces, architectures, possible grounding schemes, power quality issues, and communication systems. Furthermore, the MVDC is introduced to improve the power oscillation damping of the DG grid connection, as presented in [12] and [19]. Therefore, to improve the power oscillation of the DG connection, the MVDC grid connection is proposed and investigated in this paper.…”
Section: Figure 1 Schematic Diagram Grid Connection With Mvdc Systemmentioning
confidence: 99%
“…The MVDC in DC microgrid application is illustrated in [18], covering AC interfaces, architectures, possible grounding schemes, power quality issues, and communication systems. Furthermore, the MVDC is introduced to improve the power oscillation damping of the DG grid connection, as presented in [12] and [19]. Therefore, to improve the power oscillation of the DG connection, the MVDC grid connection is proposed and investigated in this paper.…”
Section: Figure 1 Schematic Diagram Grid Connection With Mvdc Systemmentioning
confidence: 99%
“…Small-signal stability analysis is an important technique to identify the dynamics of the AC microgrid. AC microgrids are usually comprised of VSC based DERs with active/reactive power controllers for parallel operation, dynamic loads (motor loads), passive loads, and resistive or inductive lines [130]- [132]. Extensive research studies have been carried out on small-signal analysis, voltage, and transient stability of AC microgrid to identify the dynamics of each parameter, such as controller dynamics, load dynamics, and system dynamics.…”
Section: Stability Studies Of Ac Microgridmentioning
confidence: 99%
“…In power system dynamic stability studies, the aggregated model of IMs has been considered, which does not reflect the true dynamics of IMs. Authors previous work investigated the LFO characteristics of the multiple parallel operating small IMs and a large IM of equivalent power rating [132], [274]. It was found that the multiple parallel operating IMs have multiple dominant oscillation frequencies which introduces more non-linearity into system dynamics.…”
Section: E Dynamic Performance With P − F and Q − V Droop Schemes And Dynamic Loadsmentioning
confidence: 99%
“…In this regard, in [46], using a neuro-fuzzy controller is proposed a Home Energy Management System (HEMS) to carry out day ahead management and real-time regulation; according to the inputs and outputs, this approach is considered a MIMO application. Another work can be seen in [47], where it is developed an adaptive neuro-fuzzy system based on Power Oscillation Damping (POD) controller to damp Low-Frequency Oscillations (LFOs) in hybrid AC/DC microgrids. Finally, in [48] an adaptive neuro-fuzzy control power is proposed to regulate the voltage in a distribution network when there is a variation in the load.…”
Section: ) Energy Microgridsmentioning
confidence: 99%